PENGARUH CAPITAL INTENSITY RATIO, INVENTORY INTENSITY RATIO, OWNERSHIP STRUCUTRE DAN PROFITABILITY TERHADAP EFFECTIVE TAX RATE (ETR) (Studi pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Tahun 2011 -2014) - Putri, Citra Lestari; Lautania, Maya Febrianti (Accounting Departement Economics and Business Faculty Syiah Kuala University, 2016)
The objectives of the research are to examine the effect of capital intensity ratio, inventory intensity ratio, ownership structure, dan profitability on effective tax rate (ETR) both simultaneously and partially. In this research, ownership structure variable using managerial ownership and institutional ownership. Profitability measured by using ROA (Return on Asset)..Data were collected from the financial statements of the manufacture companies that listed at Indonesia Stock Exchange. Research conduct in 4 years (2011-2014). By using purposive sampling, there are 60 companies fulfilling the sample criteria. Multiple linier regression model is used to test the hypothesis.The results of this research are capital intensity ratio, inventory intensity ratio, ownership structure, and profitability simultaneously influence on ETR. Ownership structure partially does not have affect on ETR. Partially, Capital intensity ratio and inventory intensity ratio have negative influence to ETR and profitability has positive influence on ETR.Keywords : Capital intensity ratio, inventory intensity ratio, ownership structure, profitability, and ETR.